Pengaruh Hasil Belajar Terhadap Penggunaan Media Pembelajaran Word Wall Kelas II SDN Karanganyar Gunung 02 - Oktavian, Denia Dwi; Reffiane, Fine (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research aims to determine the effect of student learning outcomes using the Word Wall application learning media on class II B students at SDN Karanganyar Gunung 02. This type of research uses experimental research in the form of Pre-Experimental Design and One Group Pretest-Posttest design. The population in this study were class II B students at SDN Karanganyar Gunung 02. The sampling technique was carried out by 28 class II B students at SDN Karanganyar Gunung 02. Data collection was obtained from tests carried out by the students. The research results showed that the average pretest result was 50.71 and the posttest result was 91.71, meaning that student learning outcomes had increased. The Paired Sample Test results obtained were 0.000<0.05, meaning that Ho was rejected and Ha was accepted and the gain-test results were obtained at 82.9, meaning that it was included in the criteria of being quite effective, which means that there is an influence on student learning outcomes on the use of the Word Wall application.